First record of Ancyronyx Erichson (Coleoptera: Elmidae) from China, with description of a new species - Bian, Dongju; Guo, Cheng; Ji, Lanzhu (Zootaxa, 2012)
Ancyronyx Erichson is recorded from China for the first time and a new species, Ancyronyx yunju sp. nov., is described from Jiangxi Province, China.